Penerapan Pendekatan Komunikasi Intersubyektif Dari Jurgen Habermas Dalam Mengomunikasikan Ajaran Alkitab Dan Berita Injil: Sebuah Refleksi Teologis - Roedy Silitonga (Sekolah Tinggi Teologi Arastamar Bengkulu, 2022)
This paper is the result of secondary research on the thoughts of Jurgen Habermas about intersubjective communication as an approach in communicating the teachings of the Bible and the Gospel message in the public sphere. This intersubjective communication puts a person in the position of being a communicator and being a communicant. The principle of equality and mutual respect is highly emphasized to find the best solution to the problems faced by humans. The purpose of writing this article is to encourage every Christian to communicate the teachings of the Bible and proclaim the Gospel message with an intersubjective communication approach in the context of religious plurality or belief and ethnic multiculturalism. Because there is a phenomenon that becomes a problem in communicating the teachings of the Bible and the Gospel message with a subject-object approach. The secondary research method used is literature study from various books and journals, followed by inductive descriptive analysis.